Pemetaan Media Luar Ruang pada Pelaksanaan Pemilihan Gubernur dan Wakil Gubernur Riau (Pilgubri) Tahun 2013 di Kota Pekanbaru - Hasanuddin; Amir Syamsuadi (Nakhoda: Jurnal Ilmu Pemerintahan, 2013)
The participation of candidates in local elections the democratic party is the dominant of the vote to win the political competition. Various attempts were made to improve the participants' tendency to choose politics. Implementation of the election for governor and vice governor of Riau Province in 2013 can not be separated from political activities such as marketing activities undertaken by all partner candidates for governor and vice governor of Riau Province. This study refers to the mapping ( mapping ) use outdoor media conducted by the regional head candidates in the election of governor and vice governor of Riau Province in 2013, especially in the city of Pekanbaru. This study used a qualitative research approach ( qualitative research ). The data will be used consists of two types of data, namely, the primary data, the data is obtained directly from respondents and observations that have been conducted and secondary data, ie data obtained from documents related to the study. Based on the results of the study concluded that the outdoor media used by candidates and prospective candidates of governor and vice governor of Riau Province in 2013 was in the form of billboards, billboards, banners and banner. The outdoor media widely installed in strategic areas in the city of Pekanbaru as junction region, area shopping centers, bridge district, area attractions, and hospitality areas.